Projecting the Road: Topological Photography on the Yunnan-Burma Frontier. (3rd July 2018) - Reisz, Emma
Abstract : This article examines photography of the Sino-Burmese border at the turn of the twentieth century. Focusing on the road between Tengyue (Tengchong) in Yunnan and Bhamo in Burma, the article considers a photographic series by Albert Pichon of the Chinese Imperial Maritime Customs to explore how the frontier was perceived and understood in the context of imperial expansion, infrastructural transformation and foreign-mediated globalization. The Maritime Customs, at the frontier between Chinese and foreign power, had a key part in controlling and conceptualizing the borders of late Qing China. This article examines photography as a projection of the topological understanding of space within the Maritime Customs, within which frontier locations were seen as a "link in the chain" and a "stage on the journey". GRAPHICAL ABSTRACT: